Effects of addition of hydrocolloids on the textural and structural properties of high-protein intermediate moisture food model systems containing sodium caseinate. Issue 8 (25th July 2017) - Li, J.; Wu, Y.; Ma, Y.; Lu, N.; Regenstein, J. M.; Zhou, P.
Abstract : High-protein intermediate moisture food (HPIMF) containing sodium caseinate (NaCN) often gave a harder texture compared with that made from whey proteins or soy proteins, due to the aggregation of protein particles. Abstract : High-protein intermediate moisture food (HPIMF) containing sodium caseinate (NaCN) often gave a harder texture compared with that made from whey proteins or soy proteins, due to the aggregation of protein particles. The objectives of this study were to explore whether the addition of hydrocolloids could soften the texture and illustrate the possible mechanism. Three kinds of hydrocolloids, xanthan gum, κ-carrageenan, and gum arabic were chosen, and samples including of these three kinds of hydrocolloids were studied through texture analysis using a TPA test and microstructure observation by confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). The texture analysis results showed that xanthan gum was more effective at softening the HPIMF containing NaCN compared to κ-carrageenan and gum arabic. In addition, with the increase of xanthan gum concentration from 0.2 to 2%, the HPIMF matrix became softer, and fractures were observed during the compression for samples with xanthan gum added at low concentrations but not 2%. Microstructure observation suggested that the matrix originally dominated by the network formed through the aggregation of swollen protein particles was inhibited by the addition of xanthan gum, resulting in the softening of the texture and also contributing to the fracture during compression. With the increase of xanthan gum concentration up to 2%, the protein dominating network would be gradually replaced with a matrix dominated by the newly formed network of xanthan gum with protein particles as fillers. Furthermore, this formation of a xanthan gum dominating network structure also resulted in changes in small molecule distribution, as observed using low-field NMR.